Strategies, uncertainty and performance of small business startups - Van Gelderen, Marco; Frese, Michael; Thurik, Roy (Kluwer, 2000)
Personal strategies of owners/founders of small business startups are related to performance and to environmental uncertainty. This is done using a longitudinal data set. Personal strategies are operationalized by a behavioral measure of the manners in which small business founders deal with situations. The results suggest a dynamic process between strategy and performance. Business owners that perform poorly employ a Reactive Strategy, with poor performance leading to increased use of reactive behavior. High performing business owners start out focussing on the most crucial issues (Critical Point Strategy), with high performance leading to a more top-down (Complete Planning) approach. These relations are controlled for characteristics of the environment of the firm. Strategy use is dependent upon the type and level of environmental uncertainty. Complete Planning strategy is used less frequently in a fast changing environment and more often in a complex environment. Use of Opportunistic Strategy is negatively related to the complexity of the environment, while the Reactive Strategy is used more frequently in a non-munificent environment.
Keywords: Strategic management; Entrepreneurship; Uncertainty; Business performance; Small business start-ups; Strategic planning; Fields of Research::340000 Economics::340200 Applied Economics